Comparative Analysis of Immunological and Hematological Indices of Patients with Septic Arthritis after Intra-Articular Injection of Glycocorticoids - Dekhtiarenko, N.O.; Panchenko, L.M.; Hrytsai, M.P.; Linenko, O.M.; Sabadosh, V.I.; Hordii, A.S. (TERRA ORTHOPAEDICA, 2022)
Summary. Subject of the research: immune status of 26 patients (main group) with septic complications after local application of glycocorticoids and 17 patients (comparative group) with septic arthritis, in which the purulent inflammatory process developed due to hematogenous spread of infection of the joint and was not a complication caused by local use of glycocorticoids.Objective: to evaluate the immune status of patients of the main and comparative groups, to study the dynamics of immunological indicators before and after surgical treatment, and to determine factors which are important to predict the disease course and treatment results.Research methods: an analysis of immunological (content of lymphocytes and their subpopulations – CD3+-, CD4+-, CD8+-cells; А, М and G classes of immunoglobulins; levels of circulating immune complexes) and hematological (levels of erythrocytes, leucocytes, thrombocytes, hemoglobin, as well as erythrocyte sedimentation rate) laboratory data of both groups was conducted.Results. Disorders concerning cellular and humoral factors of immune defense as well as hematological indices were revealed. It is shown that the improvement of immune status after clearing surgical intervention and the reduction of inflammatory response in patients of the main group is slower than in the comparative group.Conclusions. Assumption was made that glycocorticoids may be a factor that deepens and prolongs the immunosuppression that patients had before their local use.